Orzekanie merytoryczne sądów administracyjnych - Trybka, Wiktor (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The granting of administrative courts greater opportunities in substantive ruling should be assessed as unambiguously positive. One cannot agree with the views of the doctrine, which indicate that such action would be incompatible with Article 10 tripartite separation of powers and 184 of the Constitution, because it is not the question of substantive ruling in place of public administration but in connection with the activities of these bodies, and within control rights. It seems that Art. 45.1 gives a sufficient basis for changes made to the Act governing the proceedings before administrative courts. The value is to ensure full realization of one’s right to court access also in administrative court proceedings. A citizen cannot bear negative consequences in case a public administration body once again makes the unlawful decision.A step in the right direction is also granting the SAC greater possibility of passing the essential and reformation judgment, which as we can see from the data from year to year SAC does more often. It is a right thing to omit in the amendment two conditions — positive — violations of substantive law and negative — lack of infringement of the proceedings provisions, which would undoubtedly cause even greater use of Art. 188 right to proceedings before administrative courts by the SAC.
Keywords: administrative courts; proceedings before administrative courts; acquisition of substantive competence; constitution; amendment; Supreme Administrative Court